Effect Of Hydrophilic Implant Surface on Crestal Bone Level in Immediately Placed Implant: A Case Report With 6 Month Follow Up - Dr. Seethal K; Dr. Mahendra Anant,; Dr. Deepesh Kumar Gupta; Dr. Anumeha Jha; Dr. Vineeta Gupta; Dr. Ambika Thakur (The Bioscan, 2026)
This case report represents an atraumatic extraction of a fractured maxillary central incisor of left side, followed by immediate placement of hydrophilic implant (straumann aqua) in the extraction socket. definitive prosthesis was placed after 4 months of implant placement. this immediate implant placement helped in preservation of soft tissue and surrounding bone, along with better esthetics and early loading.